Psikoterapi Re-Edukasi (Konseling) Terhadap Tingkat Kecemasan Pasien Pre Operatif Sectio Caesaria - andria pragholapati; Sri Wulan Megawati; Yana Suryana (Universitas Islam Indonesia, 2021)
The research's objective is to identify the influence of re-education Psychotherapy on the anxiety level of preoperative sectio caesaria patients at central operating theater RSUD Kota Bandung. The pre experimental design with one group pre-test-post-test design. The population is preoperative sectio caesaria patients and a sample of 30 participants with purposive sampling. Used SAS/SRAS instrument to measure anxiety levels. The conclusion there was a significant influence of implementing re-education psychotherapy to preoperative sectio caesaria anxiety patient level. Based on the result of the study, re-education psychotherapy is needed in preoperative patients as a companion pharmacology.